Política antitruste e sua consistência: uma análise das decisões do Sistema Brasileiro de Defesa da Concorrência relativas aos Atos de Concentração - Cardoso, Diego Soares (Universidade Federal de São Carlos, 2013)
The goal of competition policy, also known as antitrust policy, is promoting the welfare and economic efficiency by preserving fair competition in markets. Merger control is one of the main responsibilities of antitrust institutions. Prohibitions and restrictions of merger operations affect market structures, thus making these decisions relevant to economic agents. This Master's thesis analyzes the decisions made by Brazilian antitrust institutions regarding merger processes. Data was collected from public documents issued from 2004 to 2011. Bivariate analysis, discrete choice models and classification decision trees show that these merger control decisions are consistent with Brazilian antitrust law. Consistent competition policy reduces uncertainty, aligns expectations and increases the efficiency of antitrust law enforcement. Therefore, this research contributes to better understanding Brazilian competition policy related to merger control and its decision drivers.
An analysis of the Brazilian Antitrust Policy Consistency
Keywords: política antitruste - Brasil; concentração econômica - Brasil; competição econômica; atos de concentração; CADE; modelos de escolha discreta; árvores de decisão induzidas; antitrust policy; merger control; discrete choice models; classification decision trees; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL::ORGANIZACAO INDUSTRIAL E ESTUDOS INDUSTRIAIS